SEROLOGICAL AND PARASITOLOGICAL OBSERVATIONS ON MALARIA IN SOUTHERN IRAN - Gh. H. Edrissiaon; A. Afshar (Tehran University of Medical Sciences, 1974)
In the course of serological and parasitological studies of malaria, 1,018 persons were examined. They were from four different areas (A, B, C and D) in the region of Bandar Abbas and 1-1ina), southern Iran, where malaria is still endemic. For the serological examinations, the IFAT was used with P. falciparum and P.vivax antigens. Several FA-positive reactions were observed in young children, most probably due to congenital antibodies. In areas A, B, and particularly in area C, the sero-positivity rates indicate that malaria control measures have been relatively effective in recent years. The sero-positivity related to increasing age, and virtually negative in the younger age groups. Parasitological findings how that more positives were found, by concentration technique than by the routine examination of thick blood films. This indicates that routine blood examination of fever cases is not able to show the real infection rate in areas where malaria is still endemic· A comparison between the serological readings obtained with extracts from 204 blood specimen on filter paper and those produced by genuine plasma samples has yielded practically identical results.